Lobbying and Capitalism - Tsakova, Ivka (Research Papers, 2012)
This paper has two main objectives: to make clear and explain two basic concepts (capitalism and lobbying) and their conceptual interconnection in the contemporary world. First, the capitalism is analyzed as a system – economic, social and cultural. Its origin, development and typology, based on ideas of well known authors as K. Marx, M. Weber, D. Bell, P. Drucker, A. Toffler, I. Wallernstein, J. Rifkin, D. Held, M. Castells, etc. are described in the text. The explanation of the lobbying includes genesis and development in condition of capitalism, political democracy and rule of law as well as specifics and actual lobbying activities in globalization’s conditions are revealed. Second, the specific features of lobbying, determined by contemporary global capitalism are analyzed through answers of the following questions: Who is lobbying? Who is lobbied? What is lobbying for about? How and where to lobby? There are underlined the difficulties of regulation of lobbying activities that are provoked by the nature of neo-liberal capitalism in the information, network society today. Finally, there are drowned some short conclusions about Bulgarian capitalism and lobbying during the last 20 years of transition – from „state socialism“ to capitalism and democracy.